2015
DOI: 10.5505/agri.2015.50103
|View full text |Cite
|
Sign up to set email alerts
|

Pain Levels of Orthopedic Surgery Patients and Pain Perceptions of Their Relatives and Nurses

Abstract: ÖzetAmaç: Bu tanımlayıcı araştırma, ortopedik cerrahi hastalarında ağrının hasta yakını ile hemşire tarafından algılanışının incelenmesi amacıyla gerçekleştirildi. Gereç ve Yöntem: Araştırmanın örneklemini ortopedi kliniğinde yatan 150 hasta, hastaların yanındaki 150 hasta yakını ve hastanın bakımından sorumlu 50 hemşire oluşturdu. Her hemşire araştırmaya yalnızca üç kere katıldı. Ağrı düzeyi, Görsel Analog Skala ile değerlendirildi. Hasta yakını ve hemşirenin, hastanın ağrı skalasını görmemesi sağlandı. Veril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The VAS measures pain intensity on a horizontal numerical scale with endpoints 0 (no pain) and 10 (worst possible pain). Scores between 1-4, 5-6 and 7-10 indicate mild, moderate and severe pain, respectively (Giusti et al, 2018;Yıldırım et al, 2015). The VAS score was not measured immediately after the surgery since some of the patients were still under the effects of anaesthesia, whereas others had received analgesics before leaving the operating room.…”
Section: Data Collectionmentioning
confidence: 99%
“…The VAS measures pain intensity on a horizontal numerical scale with endpoints 0 (no pain) and 10 (worst possible pain). Scores between 1-4, 5-6 and 7-10 indicate mild, moderate and severe pain, respectively (Giusti et al, 2018;Yıldırım et al, 2015). The VAS score was not measured immediately after the surgery since some of the patients were still under the effects of anaesthesia, whereas others had received analgesics before leaving the operating room.…”
Section: Data Collectionmentioning
confidence: 99%
“…Several studies measured the agreement between patient-and nurse-reported pain intensity assessment (Akin & Durna, 2013;Guner, Akin, & Durna 2014;Hall-Lord, Larssen, & Steen 1999;Horton, 2002;Hovi & Lauri, 1999;Klopfenstein, Herrmann, Mamie, Van Gessel, & Forster 2000;Nekolaichuk et al, 1999;Stephenson, 1994;Van Lancker et al, 2015;Yildirim et al, 2015). The results of these studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Pain has been defined as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage” (Task Force on Taxonomy of the International Association for the Study of Pain ) and as “pain is whatever the experiencing person says it is, existing whenever he says it does” (McCaffery, ). These definitions indicate that the patient's verbal report of pain is the single reliable indicator of pain (Yildirim et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 18 19 20 21 More specifically, studies have shown that medical professionals have a tendency to underscore patients’ pain. 17 , 22 , 23 …”
mentioning
confidence: 99%